The ADAMTS13‐von Willebrand factor axis in COVID‐19 patients. (18th December 2020) - Mancini, Ilaria; Baronciani, Luciano; Artoni, Andrea; Colpani, Paola; Biganzoli, Marina; Cozzi, Giovanna; Novembrino, Cristina; Boscolo Anzoletti, Massimo; De Zan, Valentina; Pagliari, Maria Teresa; Gualtierotti, Roberta; Aliberti, Stefano; et al.
Abstract: Background: Severe coronavirus disease 2019 (COVID‐19) is characterized by an increased risk of thromboembolic events, with evidence of microthrombosis in the lungs of deceased patients. Objectives: To investigate the mechanism of microthrombosis in COVID‐19 progression. Patients/Methods: We assessed von Willebrand factor (VWF) antigen (VWF:Ag), VWF ristocetin‐cofactor (VWF:RCo), VWF multimers, VWF propeptide (VWFpp), and ADAMTS13 activity in a cross‐sectional study of 50 patients stratified according to their admission to three different intensity of care units: low (requiring high‐flow nasal cannula oxygenation, n = 14), intermediate (requiring continuous positive airway pressure devices, n = 17), and high (requiring mechanical ventilation, n = 19). Results: Median VWF:Ag, VWF:RCo, and VWFpp levels were markedly elevated in COVID‐19 patients and increased with intensity of care, with VWF:Ag being 268, 386, and 476 IU/dL; VWF:RCo 216, 334, and 388 IU/dL; and VWFpp 156, 172, and 192 IU/dL in patients at low, intermediate, and high intensity of care, respectively. Conversely, the high‐to‐low molecular‐weight VWF multimers ratios progressively decreased with increasing intensity of care, as well as median ADAMTS13 activity levels, which ranged from 82 IU/dL for patients at low intensity of care to 62 and 55 IU/dL for those at intermediate and high intensity of care. Conclusions: We found a significant alteration of the VWF‐ADAMTS13 axis in COVID‐19 patients, with an elevated VWF:Ag to ADAMTS13 activity ratio that was strongly associated with disease severity. Such an imbalance enhances the hypercoagulable state of COVID‐19 patients and their risk of microthrombosis.